No association between hepatitis B or C viruses and vulval lichen planus in a UK population. - Cooper, S; Kirtschig, G; Jeffery, K; Wojnarowska, F (2004)
The aim of the study was to investigate the prevalence of hepatitis C (HCV) antibodies, hepatitis B surface antigen (HBsAg) carriage and liver disease in 100 females with genital lichen planus (LP) in Oxfordshire. Sera were screened for HCV antibodies (AxSYM HCV 3.0 Abbott), HBV surface antigen (AxSYM HBsAg V2 Abbott), mitochrondrial and anti-smooth muscle antibodies. Liver function tests were undertaken. All sera were negative for HCV antibody and HBsAg. Transiently abnormal liver function tests (2) and liver specific antibodies (2) were detected in four patients with no underlying liver disease. We found no association between HBV or HCV and genital LP in this population.